Financial planning awareness among youth at Permodalan Nasional Berhad (PNB) Kuala Lumpur / Akhmal Aliff Che Mahamud - Che Mahamud, Akhmal Aliff (Faculty of Business and Management, 2014)
The purpose of this research is to determine “Financial planning awareness among youth at Permodalan Nasional Berhad (PNB), Kuala Lumpur”. Financial planning is one of important factor that need to be done carefully. This is because an error in managing the financial will only waste of time and resource and can lead to bankruptcy. Thus, this paper will essentially close to find out the factors affecting youth financial awareness. The objectives of this research is to analyze the level of financial awareness among youth, to identify the relationship between financial behavior, financial knowledge and parent roles with the awareness of financial planning among youth and to determine the most influence factors towards financial awareness among youth. Besides that, this research is a quantitative research study whereby the findings of the study are analyzed by using the Statistical Package for the Social Sciences (SPSS). Next, the data collected in this research is analyzed by using reliability test, descriptive analysis, correlation analysis and regression analysis in order to achieve the research objectives. In order to obtain the findings, a set of questionnaire consists of 5 sections is distributed to 100 respondents. Result shows financial behavior have been most influence factors towards financial awareness among youth at PNB. There is also recommendation in this research which to emphasize the awareness of financial planning especially among youth.